Rapport conflictuel entre projet de soi pour soi et projet de soi pour autrui : analyse par les théories de la traduction et de la double transaction - Muriel Deltand; Mokhtar Kaddouri (Nantes Université, 2020)
The contribution mobilizes the theory of translation and that of the double transaction, which it combines to analyze the positioning of actors considered in their individual and social dynamics. Two interviews from two surveys conducted in different contexts (Congo, France) serve as a basis for this analysis. The first interview illustrates the success of translation and biographical and relational transactions, while the second illustrates the unsuccessful outcome of transactions due to divergent translation. The question that the article attempts to answer concerns the role of translation in the success of the double transaction.